Peranan Pembiayaan yang Disalurkan Perbankan Syariah Terhadap Produk Domestik Regional Bruto Sektor Industri dan Jasa di Pulau Jawa Tahun 2015-2023 - Robbi, Imam Arsya Shofa; Purwanto, Purwanto; Pudail, M. (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2025)
The Islamic banking system in Indonesia aims to support national progress by promoting justice and public welfare. One way to achieve this is by channeling financing as a source of additional capital. The availability of financing from Islamic banks can positively impact production and increase income. A region's income is often reflected in its Gross Regional Domestic Product (GRDP). This study examines the significant influence of financing from Islamic Commercial Banks (BUS) and Islamic Business Units (UUS) on the industrial and service sectors across Java Island from 2015 to 2023. This study applies a quantitative method, utilizing secondary annual data obtained online from the OJK and BPS websites. The collected data were analyzed using the panel data regression method, as the dataset combines time series and cross-sectional data. The results indicate that financing channeled by BUS and UUS in Java significantly affects the GRDP of the industrial and service sectors by 58%.